2019
DOI: 10.1021/acsaem.9b01624
|View full text |Cite
|
Sign up to set email alerts
|

Improved Morphology and Interfacial Contact of PBDB-T:N2200-Based All-Polymer Solar Cells by Using the Solvent Additive p-Anisaldehyde

Abstract: All-polymer solar cells (all-PSCs) have been intensively investigated due to their excellent thermal and mechanical stabilities. However, the efficiency of all-PSCs is still far behind that of organic solar cells (OSCs), which are based on small molecule acceptors. Improving the efficiency of all-PSCs is of great urgency. In this work, the solvent additive named p-anisaldehyde (AA) was introduced to improve the performance of all-PSCs based on PBDB-T:N2200. It is demonstrated that AA helps to form a better net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In order to understand the effect of LiF on the charge transfer in devices, we characterized the dark J – V characteristics of single charge carrier devices (ITO/ZnO/PM6:Y6/ETL/Ag or Al) and estimated the electron mobility through the space limited current (SCLC) model as shown in Figure . , The results show that the electron mobilities of PFN-Br (8.47 × 10 –4 cm 2 V –1 s –1 ) and LiF (6.41 × 10 –4 cm 2 V –1 s –1 )-based devices are lower than that of L-PFN-Br (9.17 × 10 –4 cm 2 V –1 s –1 ), and the electron mobilities of PDINO (7.31 × 10 –4 cm 2 V –1 s –1 ) and LiF (6.41 × 10 –4 cm 2 V –1 s –1 ) devices are also lower than that of L-PDINO (8.26 × 10 –4 cm 2 V –1 s –1 ). These results indicate that LiF insertion can significantly improve electronic transport.…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the effect of LiF on the charge transfer in devices, we characterized the dark J – V characteristics of single charge carrier devices (ITO/ZnO/PM6:Y6/ETL/Ag or Al) and estimated the electron mobility through the space limited current (SCLC) model as shown in Figure . , The results show that the electron mobilities of PFN-Br (8.47 × 10 –4 cm 2 V –1 s –1 ) and LiF (6.41 × 10 –4 cm 2 V –1 s –1 )-based devices are lower than that of L-PFN-Br (9.17 × 10 –4 cm 2 V –1 s –1 ), and the electron mobilities of PDINO (7.31 × 10 –4 cm 2 V –1 s –1 ) and LiF (6.41 × 10 –4 cm 2 V –1 s –1 ) devices are also lower than that of L-PDINO (8.26 × 10 –4 cm 2 V –1 s –1 ). These results indicate that LiF insertion can significantly improve electronic transport.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the common features of traditional organic solar cells, such as low cost, abundance of raw materials, and on-demand design of materials, all-polymer solar cells (all-PSCs) have drawn growing attention because of their outstanding stability and softness, which makes it possible to realize wearable electronic devices, photovoltaic integration, and other technologies. ,, In addition, it is considered to be one of the most promising fields of organic solar cells (OSCs). Recently, the power conversion efficiencies (PCEs) of all-PSCs have reached over 16%. However, its PCE still has a certain gap compared with the traditional OSCs composed of polymer donors and small-molecule acceptors. It is known that there are few high-performance polymer donor and acceptor materials, which restricts the development of all-PSCs. Furthermore, the morphological compatibility of blends is vital to reaching high-performance photovoltaics, in which continuous interpenetrating networks can achieve better exciton dissociation and carrier transport. ,, Owing to the twist of the polymer chain and low mixing entropy, the interactions between polymer donors and polymer acceptors are more complex and generally result in poor phase separation, which is harmful to exciton separation and carrier transportation. Besides, the poor utilization of solar irradiation, especially in the short wavelength region, limits the improvement in the efficiency of all-PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al investigated the effect of using p -anisaldehyde (AA) on the device performance, based on poly[(2,6-(4,8-bis-5-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-b:4,5-b′]dithiophene)-co-(1,3-di(5-thiophene-2-yl)-5,7-bis(2-ethylhexyl)benzo[1,2-c:4,5-c′]dithiophene-4,8-dione)]:poly{[N,N0-bis(2-octyldodecyl) naphthalene1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene)}(PBDB-T:N2200). They found that the interfacial contact between PBDB-T and N2200 itself and between the active layer and PEDOT: PSS improved, which led to the promotion of efficient exciton dissociation [ 41 ].…”
Section: Introductionmentioning
confidence: 99%